MARKETING STRATEGY ANALYSIS OF MICRO FINANCING PRODUCT AT MICRO, SMALL AND MEDIUM ENTERPRISES (SMES) IN BRI SYARIAH TULUNGAGUNG - Irfan Harmoko (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
Micro financing product of bank BRI Syariah, is one of financing product which be operated compatible of sharia principle thats intend to increase the volume of financing especially in micro, small and medium enterprises (SMEs).The district of Tulungagung as one of region which became the center of micro, small and medium enterprises (SMEs), that is the target market for the banking business to channel of financing. The prospects and chance are pretty big in the business segment of SMEs especially in Tulungagung, it is necessary a right marketing strategy in order to sell a micro financing product. It is this which became the basic the need for research about marketing strategy of micro financing product bank BRI Syariah Tulungagung in micro, small and medium enterprises (SMEs). The destination of this research are identification of marketing strategy was done by the company and identification of internal and eksternal environment factor wich influence the company to make a development business strategy which can applied by the company. The research was done by the survey basicly in analysis descriptive methode, that is describe the problem suitable as it is and be based the fact which is just getting underway (ex post facto). The data analysis that used is qualitative analysis methode that reduce the problem which exist with the sentence which aims to explain the problem was happened, so eventually will be found a distinct conclusion with use SWOT analysis. The result of researh indicated that marketing strategy of micro financing produtc bank BRI Syariah Tulungagung in micro, small and medium enterprises (SMEs) is aim to strategy factor (S-O) which have the highest score 2,01. This strategy can be accepted from SWOT analysis with use internal strength for exploit the opportunity which exist